A real life comparison of the effectiveness of adalimumab and golimumab in moderate-to-severe ulcerative colitis, supported by propensity score analysis. Issue 12 (December 2018) - Renna, Sara; Mocciaro, Filippo; Ventimiglia, Marco; Orlando, Rosalba; Macaluso, Fabio Salvatore; Cappello, Maria; Fries, Walter; Mendolaro, Marco; Privitera, Antonino Carlo; Ferracane, Concetta; Pisana, Valentina; Magnano, Antonio; et al.
Abstract: Background: Adalimumab and golimumab are effective in the treatment of moderate to severe ulcerative colitis. Aims: We reported the comparative effectiveness of adalimumab and golimumab in ulcerative colitis. Methods: 118 patients treated with adalimumab and 79 treated with golimumab were included and evaluated at 8 weeks and at the end of follow up. Results: Overall clinical benefit was 72.6% at 8 weeks and 58.9% at the end of follow up. Patients with longer disease duration and those treated with adalimumab had a better outcome. Clinical benefit was 78.8% in adalimumab patients and 63.3% in golimumab patients (p = 0.026) after 8 weeks; it was 66.9% in adalimumab patients and 46.8% in golimumab patients (p = 0.008) at the end of follow up. These data were confirmed by propensity score analysis. A further analysis considering adalimumab optimization as treatment failure showed that the difference between adalimumab and golimumab was not significant. Conclusion: Adalimumab and golimumab are effective in the treatment of ulcerative colitis. Adalimumab seems to be more effective than golimumab. This difference is probably affected by the impossibility of golimumab to be optimized in Italy while adalimumab is.